2013
DOI: 10.1142/s0218810413500263
|View full text |Cite
|
Sign up to set email alerts
|

OUTCOMES OF FOUR-CORNER ARTHRODESIS USING THE HUBCAPTM CIRCULAR PLATE

Abstract: We present results of four-corner carpal arthrodesis with the Acumed Hubcap circular plate performed at our unit. Eight patients underwent eight procedures over five years, for scapholunate advanced collapse (five wrists) and scaphoid non-union advanced collapse (three wrists). Outcomes included range of motion, quickDASH scores, and visual analogue scores for satisfaction. At final follow-up, mean flexion-extension arc was 56°, mean radial-ulnar deviation 29° and mean quickDASH score was 23/100. Mean score fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…This is consistent with other reported studies despite differences in technique to achieve fusion, such as the spider plate or headless screws. 14,18 This remains above the minimal motion necessary for a functional arc of motion which was described by Ryu et al 20 as being 60° of extension, 54° of flexion, 40° of ulnar deviation, and 17° of radial deviation of the wrist.…”
Section: Discussionmentioning
confidence: 83%
“…This is consistent with other reported studies despite differences in technique to achieve fusion, such as the spider plate or headless screws. 14,18 This remains above the minimal motion necessary for a functional arc of motion which was described by Ryu et al 20 as being 60° of extension, 54° of flexion, 40° of ulnar deviation, and 17° of radial deviation of the wrist.…”
Section: Discussionmentioning
confidence: 83%
“…Studies of 4-CA carried out by various techniques have shown that at up to 10 years follow-up there are generally satisfactory union rates, functional scores, and objective motion, and strength with low complication rates and revision rates to total wrist arthrodesis (Bain and Warts, 2010;Ball and Bergman, 2012;Bedford and Yang, 2010;Goldfarb et al, 2004;Gonzalez del Pino et al, 2012;Khan et al, 2013;Luegmair and Houvet, 2012;Ozyurekoglu and Turker, 2012;Rhee and Shin, 2013). However, there are reports of higher rates of complications with circular plate fixation including non-union, delayed union, and dorsal impingement (Shindle et al, 2007;Skie et al, 2007;Vance et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…19 Since then, other fixation methods have been introduced including locking and nonlocking plates. [20][21][22][23][24][25] With a variety of fixations methods described, there has been no consensus on a superior method. Each of these fixation techniques have their own efficacy and complication profile and need to be examined on their own merits.…”
Section: Discussionmentioning
confidence: 99%